Penekanan Penyakit Lincat Tembakau Temanggung dengan Streptomyces spp. - Triwidodo Arwiyanto; Kharis Haryono; Achmadi Priyatmojo; Toekidjo Martoredjo; Gembong Dalmadiyo (Universitas Gadjah Mada, 2007)
Streptomyces is one of a soil microorganisms which is rarely used by Indonesian researcher for biological control of planth pathogent. Local isolates of Streptomyces spp. were used in this study to control